Multi-criteria evaluation model: an application of MRP parameterization - David DAMAND (International Journal of Applied Methods in Electronics and Computers, 2020)
This paper presents a multi-criteria evaluation model applied to the parameterization of the MRP method. Existing optimization approaches that address this problem tend to adopt a means of simulation. A simulated solution is characterized by a pair (parameters, performance indicators). In the context of the evaluation of solutions, the work of Barth, Damand et al. (2003) propose a heuristic approach to extracting knowledge from a solution set. The approach is based on the definition of a multi-criteria solution comparison function. The objective of this paper is to present the detailed modeling of this comparison function. Ultimately, this result contributes to the formalization of a multicriteria optimization problem. A problem solving strategy is proposed.